Diffusion of Bilateral Tendencies in the Common Trade Policy of the European Union - Zdzislaw W. Puslecki (Current Aspects in Business, Economics and Finance Vol. 1, 2022)
This research study analysis the diffusion of bilateral tendencies in the European Union’s Common Trade Policy. Important tendencies in the trade regime are realistic points. Various lobbies, such as food producers’ organizations and unions, or other non-governmental organizations, including trade unions, have a substantial influence on the decisions made by representatives of nations participating in the World Trade Organization (WTO). The biggest conflicts between the United States and the European Union within WTO were caused by agricultural problems also during the Doha Round. The main objective of the research task is to give a comprehensive analysis of the diffusion of bilateral tendencies in the Common Trade Policy of the European Union. The analyzed problems were solved with the use of both quantitative and qualitative research methods. It is critical to emphasize that, on a theoretical level, knowing the trade policy options of liberalization versus protectionism is important. Despite the clear benefits of the multilateral WTO forum for trade liberalization, the rapid growth of bilateral and multilateral North-South Free Trade Areas (FTAs) begs a systematic explanation for why some forums are preferred over others.